Electronic resources management in private higher education institutions : basis for a three-year electronic resources management plan - Caranay, Ligaya N. (Saint Louis College, City of San Fernando, La Union : [s.n.], 2022)
This study utilized the descriptive survey research design. It aimed to assess the extent of practice on electronic resources management among the libraries of Private Higher Education Institutions (PHEIS) in La Union. There were 427 respondents in this study specifically, 408 library clientele and 19 library staff. Library clientele were chosen through simple random sampling and a total enumeration for the library staff. A researcher-made questionnaire was utilized to gather data. Mean and t ratio for r were used to treat the data statistically. A Three-Year Electronic Resources Management Plan was subsequently crafted to enhance the extent of practice on electronic resources management. Findings revealed that electronic resources management were practiced among libraries of PHEIs in La Union and they faced serious challenges on the electronic resources management more specifically: insufficient collection of electronic resources, internet connectivity issues, lack of budget, outdated hardware and software used, and electronic resources cannot be searched quickly. It was concluded that the PHEIs libraries manifest good practices in managing electronic resources that adhere to electronic resources management standards which could be attributed to administrative support through budget allocation, constant update on knowledge and technological know-how, and the innovation and resourcefulness of the librarians. This study recommended that the output should be adopted for implementation by the PHEIS in La Union
References: pages 146-154.
CHED-La Union
Keywords: Electronic books